Guyana : Why Has Growth Stopped? An Empirical Study on the Stagnation of Economic Growth - Gold, Judith; Atoyan, Ruben; Staritz, Cornelia (Washington, D.C. : International Monetary Fund, 2007)
After a period of exceptionally strong economic performance, Guyana's growth has stagnated since 1998. The paper tries to identify the factors that can explain this dramatic deterioration in economic performance. The paper first attempts to explain the decline of growth with a growth accounting exercise which shows that there was a significant swing in total factor productivity, and than uses a panel regression framework to analyze the growth impact of changes in various factors. Finally, through a series of cross-country exercises, the paper shows that the primary reasons for the divergence between the economic performance of Guyana and other Caribbean, HIPC, and PRGF-eligible countries in 1998-2004 are a substantial decline in share of net foreign and private domestic investment in GDP, a decline in the labor force, and a less favorable political and institutional environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet